2019
DOI: 10.1097/icb.0000000000000556
|View full text |Cite
|
Sign up to set email alerts
|

Cystoid Macular Edema Secondary to Rituximab

Abstract: Rituximab has been previously associated with macular edema. Macular edema causing visual loss shortly after receiving rituximab may respond to discontinuation of the rituximab and local steroid injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…1 DHIS occurs in 1.6% to 8% of HD patients. 3 The pathophysiological mechanism that governs DHIS is a combination of arterial steal syndrome, which results in hypoperfusion distal to the anastomosis, 1,2 and increased resistance to blood flow when there is arterial stenosis in the arm 4 and distal arteriopathy. 5 The current management of DHIS is split into percutaneous and surgical approaches.…”
Section: Success Of Rheopheresis To Treat Digital Hypoperfusion Ischemic Syndromementioning
confidence: 99%
See 3 more Smart Citations
“…1 DHIS occurs in 1.6% to 8% of HD patients. 3 The pathophysiological mechanism that governs DHIS is a combination of arterial steal syndrome, which results in hypoperfusion distal to the anastomosis, 1,2 and increased resistance to blood flow when there is arterial stenosis in the arm 4 and distal arteriopathy. 5 The current management of DHIS is split into percutaneous and surgical approaches.…”
Section: Success Of Rheopheresis To Treat Digital Hypoperfusion Ischemic Syndromementioning
confidence: 99%
“…2 The third patient treated with rituximab for IgG4-related disease of the face and sinuses developed bilateral macular edema 6 weeks after rituximab infusion followed by successful intravitreal triamcinolone treatment. 3 Six weeks after rituximab infusion for ABMR treatment our patient was diagnosed with macular edema of the right eye. With other possible causes excluded and good response to intravitreal triamcinolone injection, rituximab remains most likely cause of macular edema in F I G U R E 1 Macular edema of the right eye our patient.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Case reports and small case studies have shown that rituximab may be an effective option for the management of noninfectious uveitis and UME, when conventional or other immunomodulatory treatment fails to control the inflammation 140,141. Despite the mostly positive evidence, some recent case studies reported the development of ME after rituximab administration for the treatment of Wegener’s granulomatosis and an IgG4-related disease of the sinuses 142,143. The use of rituximab is considered relatively safe, with most AEs being transient reactions to the infusion.…”
Section: Introductionmentioning
confidence: 99%